1995
DOI: 10.1002/j.1460-2075.1995.tb07107.x
|View full text |Cite
|
Sign up to set email alerts
|

Multimerization and transcriptional activation of the phosphoprotein (P) of vesicular stomatitis virus by casein kinase-II.

Abstract: Casein kinase‐II (CK‐II) is a widely distributed protein kinase, which plays numerous roles in the regulation of transcription through modification of transacting transcription factors. Phosphorylation of vesicular stomatitis virus (VSV) P protein by CK‐II was found to be both necessary and sufficient for transcriptional activation. Upon treatment of P by CK‐II, activity was acquired faster (t1/2 = 3.7 min) than were total phosphates (t1/2 = 7.4 min). Stoichiometry was 2 mol phosphate/mol P, indicating activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
131
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(140 citation statements)
references
References 31 publications
8
131
1
Order By: Relevance
“…Studies on a number of viruses ranging from rhabdovirus to paramyxovirus report a different oligomeric status of P protein including dimer, trimer, and tetramer (9,(11)(12)(13)17). By gel filtration, DLS, and chemical cross-linking analyses, we have shown that the RPV P protein exists as a tetramer in solution, and the tetramerization is through the coiled coil region of the C-terminal domain.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Studies on a number of viruses ranging from rhabdovirus to paramyxovirus report a different oligomeric status of P protein including dimer, trimer, and tetramer (9,(11)(12)(13)17). By gel filtration, DLS, and chemical cross-linking analyses, we have shown that the RPV P protein exists as a tetramer in solution, and the tetramerization is through the coiled coil region of the C-terminal domain.…”
Section: Discussionmentioning
confidence: 85%
“…Although earlier work on P proteins from SeV, NDV, and MuV suggested that P could be a trimer, recent structural analyses using various biophysical methods and crystallographic study reveal that SeV P is a tetramer (13,21). Though VSV P protein is reported to be a trimer, it is also suggested to form a tetramer (9,11). It might be noted that the study with rabies virus (a rhabdovirus) P also does not exclude the possibility of tetramer formation (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that oligomer formation facilitates movement of P (and most likely of the complete polymerase complex) on the RNA template, thereby maintaining polymerase processivity (4). A requirement of P oligomers for viral RNA synthesis was also described for P proteins of other viruses of the order Mononegavirales, including vesicular stomatitis virus (10,11) and human parainfluenza virus type 3 (12). For the P protein of Sendai virus and human parainfluenza virus type 3, a defined coiled coil region is sufficient for oligomer formation (8,13).…”
mentioning
confidence: 93%
“…For the P protein of Sendai virus and human parainfluenza virus type 3, a defined coiled coil region is sufficient for oligomer formation (8,13). By contrast, vesicular stomatitis virus P oligomerization only occurs prior to phosphorylation of two amino acid residues in the N-terminal acidic region (11). Interestingly, phosphorylation-negative vesicular stomatitis virus P mutants are fully active in replication but defective in transcription (14), suggesting that the viral transcriptase and replicase are two distinct entities with different subunit composition.…”
mentioning
confidence: 99%